Roles of the uvsC, uvsD, uvsE, and mtcA genes in the two pyrimidine dimer excision repair pathways of Deinococcus radiodurans. - Evans, D M (1983)
In Deinococcus radiodurans, the genes uvsC, uvsD, uvsE, and mtcA are all involved in the single-strand incision of UV-irradiated DNA, and mutations in at least two of them were required to produce an incisionless strain. One mutation must be in mtcA and one in uvsC, uvsD, or uvsE. Strains carrying single mutations in any one of the genes can incise DNA to the same extent as the wild-type strain. Neither the presence of EDTA nor the absence of protein synthesis affected the incision step. Strains deficient in DNA incision have greatly reduced DNA degradation after UV irradiation, and upon addition of chloramphenicol to the postirradiation medium, they do not undergo excessive DNA degradation as is seen in the wild-type strain and strains singly mutant in uvsC, uvsD, or uvsE. The strain singly mutant in mtcA also lacked chloramphenicol-enhanced DNA degradation and loss of viability but behaved similarly to the wild-type strain with respect to resumption of DNA synthesis and DNA degradation in the absence of chloramphenicol. It is proposed that two constitutive, cation-independent UV endonucleases are present in D. radiodurans: UV endonuclease alpha (the product of the mtcA gene), which incises in response to pyrimidine dimers, mitomycin C cross-links, bromomethylbenzanthracene adducts, and other alkylation damage, and UV endonuclease beta (the product of the uvsC, uvsD, and uvsE genes), which incises only in response to pyrimidine dimers. Both endonucleases have associated exonuclease activity.(ABSTRACT TRUNCATED AT 250 WORDS)